2017
DOI: 10.3390/buildings7030077
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Densified Polystyrene and Unprocessed Fly Ash on Concrete Engineering Properties

Abstract: Abstract:The present study evaluated the combined effects of two types of waste materials of expanded polystyrene (EPS) and unprocessed fly ash (FA) on different properties of concrete. A novel recycling technique of densifying waste EPS is used to produce a novel lightweight aggregate (LWA). This new technique has solved the problem of segregation in concrete by coating EPS particles with a natural binder of clay and cement. Nine different concrete mixtures with a water to cement ratio of 0.8 were used. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…According to [4,5], choosing lower substitutions of EPS in concrete mixture is within satisfactory limits. However, one of the main goals of the present work is to utilise as much EPS aggregate as possible, solving the disposal problem of waste expanded polystyrene foam and producing light-weight concrete blocks with low thermal conductivity in construction the High-Rise buildings.…”
Section: Concrete Mixturesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [4,5], choosing lower substitutions of EPS in concrete mixture is within satisfactory limits. However, one of the main goals of the present work is to utilise as much EPS aggregate as possible, solving the disposal problem of waste expanded polystyrene foam and producing light-weight concrete blocks with low thermal conductivity in construction the High-Rise buildings.…”
Section: Concrete Mixturesmentioning
confidence: 99%
“…As we know, EPS aggregate is a light-weight material. Therefore, it can be partially replaced volume of concrete mixture to produce light-weight concrete, which is an important material in reducing the dead-weight of concrete complying with special concrete structures of high-rise buildings [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…As the EPS-beads' content increases directly, the concrete density decreases. That occurs because the density of EPS-beads is much less than that of natural rocky coarse aggregate [2]. The density variations also occur due to the variations in the entrapped air content against the different EPS-beads' dosage contents.…”
Section: Effect Of Eps Beads On Densitymentioning
confidence: 99%
“…Due to this, in the present research, the velocity values are high because due to the increasing volume of EPS-beads the entrapped air voids increased, which also decreased the strength and velocity values. An investigation into the engineering properties of concrete reported that as a consequence of the cement-water hydration as a consequence of the cement-water hydration process over curing time, the physical and chemical changes will occur in the concrete and will increase the strength and density and, as a result, will increase the UPV values of concrete [2,60].…”
Section: Eps (%) and Researchersmentioning
confidence: 99%
See 1 more Smart Citation